Transformasi Peran HR Business Partner di Era Generative AI: Tinjauan Literatur 2018–2025 - Eko Sudarso (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid advancement of Generative Artificial Intelligence (Generative AI) since 2022 has significantly transformed human resource management practices, particularly the role of Human Resource Business Partners (HRBPs), who serve as strategic partners in organizational decision-making. Despite growing literature on HR digitalization, research specifically examining the impact of Generative AI on HRBP roles remains limited. This study aims to map existing research on HRBP and Generative AI, analyze changes in HRBP roles and competencies, and identify emerging challenges and opportunities in the era of generative technologies. Employing a systematic literature review, the study examines scientific publications from 2018 to 2025 across multiple reputable databases. Findings reveal that Generative AI shifts HRBP responsibilities from traditional administrative and consultative functions toward strategic roles enhanced by AI-driven analytics. Emerging competencies, including AI literacy, data-driven consulting, and ethical decision-making, are increasingly crucial for effective HRBP performance. The study also highlights risks such as algorithmic bias, privacy concerns, and the need for ethical governance frameworks. Overall, this research provides a conceptual framework for the transformation of HRBP into an AI-augmented model and offers directions for future studies on integrating AI into strategic human resource functions.